The relationship between dominant follicle development and clinical outcomes of hormone replacement therapy-frozen embryo transfer: a retrospective clinical study - Huang, Chenyang; Shen, Xiaoyue; Yan, Yuan; Shan, Huizhi; Shi, Qingqing; Mei, Jie; Xing, Jun (Frontiers in Endocrinology, 2023)
Research question: Hormone replacement therapy (HRT) is one of the most used endometrial preparation protocols for frozen embryo transfer (FET) due to the convenience of its administration and stability of pregnancy outcomes. There are several HRT cycles accompanied by the development of dominant follicles. However, the relationship between dominant follicle development and clinical outcomes in HRT-FET cycles remains unclear. Design: We carried out a retrospective cohort study of 13251 cycles at our reproductive medicine center from 2012 to 2019. Total cycles were divided into two groups according to whether there was dominant follicular development. In addition, we conducted a secondary analysis that used propensity-score matching to reduce confounding variables. A univariate and multivariable logistic regression model was further employed to analyze the effect of dominant follicle development in HRT cycles on clinical pregnancy outcomes. Results: There was no significant correlation between dominant follicle development in HRT-FET cycles and the clinical pregnancy rate (adjusted OR = 1.162, 95% CI: 0.737-1.832, P = 0.52). In addition, there was a positive correlation between the basic follicle-stimulating hormone (FSH) level and the development of dominant follicles, while there was a negative correlation between antral follicle count (AFC), menstrual cycle length and the development of dominant follicles in HRT cycles. Conclusions: The development of dominant follicles in HRT-FET cycles does not affect the clinical pregnancy rate, early miscarriage rate and live birth rate. Therefore, it is not necessary to immediately cancel the FET cycle immediately when dominant follicle development is monitored in the HRT-FET cycle.